112k views
3 votes
O A. g(x) = -2*O B. g(x) = -|X1O C. g(x) = - x2O D. g(x) = - x

O A. g(x) = -2*O B. g(x) = -|X1O C. g(x) = - x2O D. g(x) = - x-example-1
User Almazik G
by
6.2k points

1 Answer

6 votes

Due to its shape, and its asymptotic tendency to go towards 0 as x goes to minus infinity and go towards infinity as x goes to infinity, the graph presented seems to be an exponential function, an exponential function has the following form:


\begin{gathered} f(x)=a^x \\ f(x)=-a^x \end{gathered}

The only exponential function included is g(x) = -2*, then, this function is the one that represents the graph, one way to quickly prove it is by replacing 0 for x into the function, as you can see in the graph, the curve goes through (0, -1), then when we replace 0 for x into the function we should get -1, like this:


\begin{gathered} g(0)=-2^0 \\ g(0)=-1 \end{gathered}

Then, the correct answer is option A

User Gero
by
5.8k points